Moral Reflections on Strict Liability in Copyright - Goold, Patrick R. (The Columbia Journal of Law & the Arts, 2021)
Accidental infringement of copyright is a pervasive and largely ignored problem. In the twenty-first century, it has become increasingly easy to infringe copyright unintentionally. When such accidental infringement occurs, copyright law holds the user strictly liable. Prior literature has questioned whether the strict liability standard is normatively defensible. In particular, prior literature has asked whether the strict liability standard ought to be reformed for economic reasons. This Article examines the accidental infringement problem from a new perspective. It considers whether it is fair to hold copyright users strictly liable for accidental infringements of copyright. This Article argues that the strict liability standard is not fair because it results in copyright users being held liable for accidents for which they are not morally responsible. Using the moral philosophy literature on responsibility, this Article explores our intuitions surrounding copyright’s liability standard in order to better understand why strict liability in this context seems “harsh” and “inequitable.” In turn, this provides an argument for reforming copyright’s liability rule and adopting a negligence standard. This Article then argues that, within the United States, the proposed reform to copyright’s liability rule should be accomplished by modifications to the existing fair use doctrine.